Analysis Of Factors Related To The Incidence Of Stunting In Children Aged 2-5 Years In Purwoasri Village, Purwoasri District, Kediri Regency - Renanda; Reny Maretha Sari (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2024)
Stunting is chronic malnutrition caused by lack of nutritional intake for a long time due to feeding that is not in accordance with nutritional needs. Indonesia is the country with the 2nd place that has a prevalence of stunting children in Southeast Asia, which is 26.92% in 2020. The purpose of this research is to determine the behavioral factors of breastfeeding, knowledge about diet and access to information with the incidence of stunting. This type of research is quantitative research with an analytical observational research design with a Cross Sectional design. The population in this study was 90 children aged 2-5 years in Purwoasri Village. With a total sample of 74 children taken by simple random sampling technique. The data analysis used was univariate, bivariate using Chi Square test. The results of this study showed a relationship between the behavior of breastfeeding with a p-value of 0.003 < 0.05, there was a relationship between dietary knowledge with a p-value of 0.006 < 0.05, there was a relationship between access to information and the incidence of stunting p-value 0.001 < 0.05. The active role of influential people in the environment is needed to invite and provide motivation and assistance from local health workers in providing health education to increase mothers' knowledge, especially about stunting.